ANALISIS KADAR LOGAM Cu DALAM BAKTERI SIMBION PADA SPONS Callyspongia sp - Adriani Adriani; Alfian Noor; Abdul Rauf Patong; Maming Gaffar (Hasanuddin University, 2012)
This research aims to analyze the levels of copper (Cu) in the sponge symbiont bacterial. The research was carried out through the steps of isolation, identification, and measurement of the metal content. Sponges used in this research is of Callyspongia sp. Bacteria were isolated from Callyspongia sp sponges in the Bacillus sp gram-positive. By using Atomic Absorption Spectrophotometer, the results showed that the levels of Cu for Callyspongia sp is 8.9112 ppm, while in the extracellular bacterial isolates Cu level ranging between 1.4009 ppm and 2.0336 ppm and in the intracellular is between 0.4786 ppm and 1.7813 ppm. It is concluded that bacterial isolates either in extra- as well as intracellular were both accomodated copper in their bodies.